Assessment of Quality of Work Life Among Nurses of Tishreen University Hospital - طويل , علاء محمود; اصبيره , ولاء هاشم (Latakia University Journal -Medical Sciences Series, 2022)
The study aimed to assess the level of quality of work life for Tishreen University Hospital nurses. The sample consisted of (200) male and female nurses working in Tishreen University Hospital, who were present during the data collection and agreed to participate in the study (convenience sample). The researchers used the Brokks & Anderson (2005) tool to assess the level of quality of working life of nurses. After the data were collected and unloaded, they were statistically processed and tabulated using the statistical program SPSS version (20). The most important results of the study were: The level of quality of work life of Tishreen University Hospital nurses was generally poor. The level of quality of work life axes for Tishreen University Hospital nurses ranged between weak and medium. The quality level of the work world and working life/home life axis was weak, and the quality of the work environment and work design was moderate. There is no statistically significant relationship between the quality of work life of Tishreen University Hospital nurses and their demographic data (department, gender, age, educational qualification, years of nursing experience, years of work in the current department, and family status).